LEFT VENTRICULAR THROMBUS IN PATIENTS WITH ACUTE ANTERIOR WALL MYOCARDIAL INFARCTION - din, Mir Jalal-ud-; Jadoon, Raheel Jahangir; Qureshi, Asfandyar; Khan, Sher Ali; Anwar, Syed Abbas; Haroon, Muhammad Zeeshan (Journal of Ayub Medical College Abbottabad, 2014)
Background: Left ventricular thrombus (LVT) is a frequent and potentially dangerous complication of acute myocardial infarction and is associated with increased risk of systemic embolization. This study was conducted to determine the frequency of left ventricular thrombus in patients with acute anterior wall myocardial infarction. Methods: This descriptive cross-sectional study was conducted in departments of Medicine and Cardiology, Ayub Teaching Hospital, Abbottabad, from 15th April to 15th October, 2011. Patients diagnosed with acute anterior myocardial infarction (MI) of all ages and either gender were included in the study on the basis on non-probability consecutive sampling. The data was collected through a structured pro forma and analysed using SPSS-16. Results: A total of 85 patients with acute anterior wall MI were studied, 58(68.2%) were males and 27(31.8%) were females. The mean age for males was 58.72±12.13 years and for females it was 59.69±8.17 years. On echocardiography 29 patients had LVT (34.1%). Mean age of patients with LVT was 61.14±10.74 and those without LVT 57.93±11.05 years. Among the 65 ST-elevation MI (STEMI) patients 28 (43.1%) got LV Thrombus and in 20 non-ST-elevation MI (NSTEMI) patients only 1(5%) had LVT. In 52 patients who were diagnosed within 12 hours of onset of chest pain 8 (15.4%) developed LVT. While in 33 patients whose MI was diagnosed after 12 hours of onset of chest pain 21 (63.6%) were complicated with LV Thrombus. Conclusion: The incidence of LVT after acute anterior MI in our population is quite significant. Male patients, older than 50 years of age, suffering from STEMI may be at increased risk of post infarct LVT. Early hospitalization seems to lower the risk of LVT. Keywords: Anterior Wall Myocardial Infarction Left Ventricular Thrombus, Acute Coronary Syndrome